2022
DOI: 10.1242/dev.199914
|View full text |Cite
|
Sign up to set email alerts
|

Human iPSC-derived cerebral organoids model features of Leigh syndrome and reveal abnormal corticogenesis

Abstract: Leigh syndrome (LS) is a rare, inherited neurometabolic disorder that presents with bilateral brain lesions caused by defects in the mitochondrial respiratory chain and associated nuclear-encoded proteins. We generated human induced pluripotent stem cells (iPSCs) from three LS patient-derived fibroblast lines. Using whole-exome and mitochondrial sequencing, we identified unreported mutations in pyruvate dehydrogenase (GM0372, PDH; GM13411, MT-ATP6/PDH) and dihydrolipoyl dehydrogenase (GM01503, DLD). These LS p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
23
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(28 citation statements)
references
References 164 publications
(181 reference statements)
0
23
0
Order By: Relevance
“…3a) 26 . The other is a frameshift mutation (79delC) in pyruvate dehydrogenase (PDHA1), which is a key subunit of the pyruvate dehydrogenase complex (PDHc) that catalyzes the conversion of pyruvate to acetyl-coA to drive the activities of the TCA cycle and electron transport chain (ETC) 27 . Both mutations may be critical drivers of LS pathogenesis (see Discussion).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…3a) 26 . The other is a frameshift mutation (79delC) in pyruvate dehydrogenase (PDHA1), which is a key subunit of the pyruvate dehydrogenase complex (PDHc) that catalyzes the conversion of pyruvate to acetyl-coA to drive the activities of the TCA cycle and electron transport chain (ETC) 27 . Both mutations may be critical drivers of LS pathogenesis (see Discussion).…”
Section: Resultsmentioning
confidence: 99%
“…These changes are more likely due to increased proton translocation into the Mt matrix that promotes the earlier steps of OXPHOS. Second, a recent analysis of genomic DNA determined that GM13411 also contains a frameshift mutation in pyruvate dehydrogenase (PDHA1) which is a key subunit of the pyruvate dehydrogenase complex (PDHc) 27 . Since PDHc catalyzes the conversion of pyruvate to acetyl-coA that enters the TCA cycle to drive the activity in complex I and II, the PDHA1 allele is expected to significantly reduce oxidative respiration.…”
Section: Discussionmentioning
confidence: 99%
“…Single-cell sequencing confirmed that the organoids remained genetically stable along with their morphology for up to 6 months, regardless of their genetic background. Other groups have also shown reproducibility of organoids as a stable model for studies of late stages of neuronal development (Giandomenico et al, 2021), and use for neurological disorders, including ALS (Pereira et al, 2021), Alzheimer's (Ghatak et al, 2019), and Leigh syndrome (Romero-Morales et al, 2020). The challenges ahead include consistency of the cellular and non-cellular components, the incorporation of vascular elements, immune cell, and other disease-relevant cell types (e.g., Schwann cells).…”
Section: Three-dimensional Culturesmentioning
confidence: 99%
“…Although the study by Yoon and colleagues reports partial amelioration of ataxia and spontaneous motor activity, the effect of NR on coordination and, most importantly, lifespan is currently unknown. Second, with respect to iPSC studies, it remains to be seen whether NR may improve the identified defects in human neuronal morphogenesis 2,3 or whether it may impact the beating activity of CM or the firing properties of neurons. Moreover, despite the general validity of the findings presented in the paper, it remains unclear why only a fraction of LS patients incurs into heart dysfunction.…”
mentioning
confidence: 99%
“…iPSCs have been previously used to investigate the neuronal phenotypes of Mechanisms by which nicotinamide riboside (NR) rescues LS models LS, as three-dimensional brain organoids showed defects in morphogenesis and cellular architecture. 2,3 However, cardiac-related aspects were not addressed.…”
mentioning
confidence: 99%